INTERNATIONAL STANDARDS ON THE INSTITUTION OF CONFISCATION IN CRIMINAL PROCEEDINGS - Polvonov Najmiddin Asliddinovich, (Scholar Express Journals, 2023)
This article analyzes the existing norms in international legal documents related to the regulation and application of the institution of confiscation. The norms in the field of confiscation of criminal assets established in the international documents adopted by the Council of Europe, UN, European Union, Organization for Economic Cooperation and Development as well as other international organizations and their bodies are analyzed in depth. Based on the results of the analysis, conclusions were drawn on the application of measures related to confiscation of assets in criminal proceedings, and proposals and recommendations for national legislation were developed
Keywords: confiscation; international standards; special confiscation; weapons of crime